Diffuse scattering model for human brain wave (Alpha) propagation prediction during meditation inside a temple, through ray tracing, a hypothetical study - Bharti, Madhulika; Bharti, Priyanka; Kumar, Manindra; Kumar, Prashant (International Multidisciplinary Research Journal, 2021)
Electromagnetic radio waves have been propagating for billions of years through the universe since the beginning of time. Electromagnetic radio wave propagation and the communication revolution it spawned, however are products of the twentieth century. Radio propagation in a particular environment is a complex, multipath phenomenon which involves several different mechanisms. According to a traditional, simplified approach, two major urban propagation mechanisms are identified over-roof-top (ORT) or vertical propagation (VP), where one major radial path undergoes multiple diffractions on building tops, and lateral propagation (LP) where several rays reflect/diffract all vertical building walls/edges according to the geometrical Optics (GO) rules before reaching the receiver.